Self-Management and Quality of Life Among Patients with Decompensated Liver Cirrhosis (Medical Forum Monthly, 2023)
Objective: To assess the effect of nursing intervention on knowledge about self-management and quality of life among patients with decompensated liver cirrhosis.Study Design: Quasi-experimental studyPlace and Duration of Study: This study was conducted at the Department of Gastroenterology, Bahawal Victoria Hospital Bahawalpur, Punjab, Pakistan from 1st April to 30th September 2022.Materials and Methods: Thirty two who are diagnosed cases of decompensated liver cirrhosis, aged between 30 to 60 years of both genders were enrolled. After taking the informed consent from patient’s intervention was given to patients as they were enrolled in study. The research scholar developed an interventional program. The post data was collected after the one month of intervention and was compared with pre-data to find out effect on knowledge about self-management and quality of life. Post assessment was done with the help of same questionnaires. Two questionnaires used for data collection Self-management knowledge questionnaire and CLDQ.Results: Six (18.8%) were between the age group 21-40 years and 26(81.3%) were in the age between 41-60 years. Majority of the patients were females 17 (53.1%) were below primary education 21(65.6%). The findings revealed that there was a significant difference between the pre and the post interventional knowledge’s score among patients regarding self-management and their Quality of life measure by CLDQ was also improved (p value <0.001).Conclusion: The educational intervention has a positive effect on decompensated liver cirrhosis patients' quality of life and self-management skills. Moreover, the liver disease education intervention is beneficial in increasing patient and family knowledge.